Silver(I) dicyanonitrosomethanide, Ag[ONC(CN)2] complex as catalyst for the selective oxidation of styrene to benzaldehyde - Mohamed Iqbal, Mohammad Anwar; Nazri, Muhammad Zulhelmi; Ahmad, Mohammad Norazmi; Abdullah, Erna Normaya; Mohamad Haziz, Umie Fatihah; Razali, Mohd Rizal; Adam, Farook (UiTM, 2020)
Silver(I) dicyanonitrosomethanide, Ag[ONC(CN)2] represent a 3D interwoven coordination polymer organization in which all the donor atoms of the functional groups of ONC(CN)2- are coordinated to the Ag(I). Oxidation of styrene utilizing H2O2 as an oxidant in acetonitrile (CH3CN) was used as a model reaction to investigate the catalytic potential of the Ag(I) complex. The CH3CN was chosen as the solvent based on the data collected from Conductor like Screening Model for Real Solvents (COSMO-RS) study. The data indicate that the Ag[ONC(CN)2] complex was compatible and soluble in CH3CN. Different parameters such as styrene:H2O2 molar ratio, reaction time, catalyst mass, and reaction temperature were studied. Highest styrene conversion (36%) with 100% selectivity towards benzaldehyde (BZ) was achieved when 25 mg catalyst, 1:1 styrene to H2O2 molar ratio were used. The reaction was carried out at 303 K for 3 h. The catalytic conversion of styrene to BZ is proposed to take place via [Ag-H2O2] adduct with styrene oxide (StO) as an intermediate. Molecular Electrostatic Potential (MEP) shows that the Ag atom has the highest probability to coordinate with the oxygen atom of H2O2. The MEP data confirms the proposed mechanism.